2018
DOI: 10.5350/sleep.hypn.2017.19.0154
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Quality with Socio-Demographic Characteristics in Elderly Referred to Health Centers in Qazvin, Iran

Abstract: Background and aim: Sleep disorders are not innately harmful to quality of life, they can induce or complicate physical and mental sicknesses and increase the risk of mortality. The aim of this study was to determine the association of sleep quality components with socio-demographic characteristics in elderly people in Qazvin, Iran. Materials and Methods: This descriptive cross-sectional study was performed on 400 elderly patients referred to health centers in Qazvin. Data were collected by using a demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…This study also was disagree with the study from Iran, which the study focus on association of sleep quality and socio-demographics characteristics in elderly referred to health centers, found that older women had worse sleep quality compared to older men (Dehghankar et al, 2018). However, the study concluded that there is no difference between older women and older men in sleep duration, habitual sleep efficiency, and sleep disturbances.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…This study also was disagree with the study from Iran, which the study focus on association of sleep quality and socio-demographics characteristics in elderly referred to health centers, found that older women had worse sleep quality compared to older men (Dehghankar et al, 2018). However, the study concluded that there is no difference between older women and older men in sleep duration, habitual sleep efficiency, and sleep disturbances.…”
Section: Discussioncontrasting
confidence: 91%
“…Iranian scholars supported it, where their study also found that there is no significant difference between education status of the elderly and their sleep quality. However, the study also reported that the elderly with lower education had poorer sleep quality (Dehghankar et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…One of the most important factors in the life of diabetic patients is their sleep quality; because sleep disturbance has an adverse effect on their performance, as well as their physical and mental health. Sleep quality is a mental index related to sleep experiences, such as satisfaction with sleep and a sense of vitality from it [17]. Insomnia has a two-way relationship with the prevalence and incidence of diabetes, it can sometimes be secondary to diabetes or it can be a cause for diabetes itself.…”
Section: Introductionmentioning
confidence: 99%
“…A study of self-care activities by older people in the United States [57], as well as another of older people living in a rural community in South Korea [58], found that the lower the level of education attainment, the higher the rate of insomnia. However, an Iranian study of sleep quality in healthy older people found no association between the prevalence of sleep disorder and the highest level of educational attainment [59]. Thus, the association between education attainment and sleep quality is inconsistent.…”
Section: Discussionmentioning
confidence: 99%